Correlative cryo‐imaging of the cellular universe with soft X‐rays and laser light used to track F‐actin structures in mammalian cells. Issue 12 (30th November 2021) - Koronfel, Mohamed; Kounatidis, Ilias; Mwangangi, Dennis M.; Vyas, Nina; Okolo, Chidinma; Jadhav, Archana; Fish, Tom; Chotchuang, Phatcharin; Schulte, Albert; Robinson, Robert C.; Harkiolaki, Maria
Abstract : A 3D cellular imaging platform developed at beamline B24 at Diamond Light Source has been used to identify cellular features such as filamentous actin in mammalian cells. This approach enabled virtual same‐sample imaging of structures captured on separate microscopes through rigid transformation of 3D data in silico, bypassing the need for additional sample processing and ensuring artefact‐free data correlation. Abstract : Imaging of actin filaments is crucial due to the integral role that they play in many cellular functions such as intracellular transport, membrane remodelling and cell motility. Visualizing actin filaments has so far relied on fluorescence microscopy and electron microscopy/tomography. The former lacks the capacity to capture the overall local ultrastructure, while the latter requires rigorous sample preparation that can lead to potential artefacts, and only delivers relatively small volumes of imaging data at the thinnest areas of a cell. In this work, a correlative approach utilizing in situ super‐resolution fluorescence imaging and cryo X‐ray tomography was used to image bundles of actin filaments deep inside cells under near‐native conditions. In this case, fluorescence 3D imaging localized the actin bundles within the intracellular space, while X‐ray tomograms of the same areas provided detailed views of the local ultrastructure. Using this new approach, actin trails connecting vesicles in the perinuclear area and hotspots of actin presence within and around multivesicular bodies were observed. The characteristic prevalence of filamentous actin in cytoplasmic extensions was also documented.